(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
The signals, exploited by the radar sensor networks and remote control systems, have to provide simultaneously high range resolution and ability to work stable in a hostile radio electronic environment. An effective approach for satisfying of these requirements is the frequent change of many different signals, which autocorrelation functions have small sidelobes. Accounting this situation in the paper the generalizations of the skew-symmetric sequences with odd lengths, which are phase manipulated signals, possessing high autocorrelation merit factor, are explored. As a result, two methods for synthesis of infinite families of phase manipulated signals with good autocorrelation properties are substantiated.